Contribution of VKORC1 and CYP2C9 polymorphisms in the interethnic variability of warfarin dose in Malaysian populations - Gan, G.G.; Phipps, M.E.; Lee, M.M.T.; Lu, L.S.; Subramaniam, R.Y.; Bee, P.C.; Chang, S.H. (Springer Verlag (Germany), 2011)
Within the Asian populations, Indian patients had been reported to require higher warfarin dose compared with the Chinese and Malay patients, and this could not entirely be explained by cytochrome P450 (CYP)2C9 gene variants. Genetic variants of vitamin K epoxide oxidase reductase complex subunit 1 (VKORC1) has been well established as one of key determinants in the different responses of warfarin amongst patients. Adult patients who attended an anticoagulation clinic with stable INR were recruited. VKORC1 and CYP2C9 genotype were sequenced, and clinical characteristics were assessed. A total of 91 Malays, 96 Chinese, and 46 Indian patients were recruited. The mean age was 55 years and 51.5% were males. The mean dose of warfarin for all patients was 3.7 mg, and the mean daily dose of warfarin was significantly higher in Indians compared with the Chinese and Malay patients, 4.9 versus 3.5 and 3.3 mg, respectively (p < 0.001). VKORC1 GG genotype was more commonly seen in Indian patients. The mean warfarin dose in patients with GG genotype required a significant higher warfarin dose compared with those with AG and AA genotype (4.9 vs. 3.7 vs. 3.1 mg, respectively; p < 0.001). CYP2C9*2 and *3 is associated with a lower maintenance dose, 2.9 versus 3.7 mg in CYP2C9*1; p < 0.01. In multivariate analysis, age, ethnic groups, and genotypes had a significant influence on the required warfarin dose. In conclusion, VKORC1 and CYP2C9 polymorphism contribute to the difference dose requirement amongst the patients but other additional possible factors may play a role in the Indian race.